(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
This article describes the importance of leguminous crops in the national economy, the role of this crop in increasing soil fertility, systematics, morphology, biology, and basic and short- term agrotechnics of the mush crop.